Influência da sustentabilidade e da inovação na intenção empreendedora de universitários brasileiros e portugueses - Paiva, Luis Eduardo Brandão (2017)
This study consists of analyzing the influence of sustainable and innovative behavior on the entrepreneurial intention of Brazilian and Portuguese university students. It also seeks to develop a model that allows predicting entrepreneurial intent from the profile of university students and their sustainable and innovative behavior. The proposed model is based mainly on the theory of behavior planned for the entrepreneurial intention, in the theory of adaptation-innovation with the purpose of investigating the innovative behavior, in front of the cognitive style of the individual, and in the sustainable dimension, which is based on Behavioral scales focused on environmental issues. This research is developed through an exploratory survey, applied with university students from the Federal University of Ceará (Brazil) and the University of Algarve (Portugal), from a cross-cultural perspective. Statistical analysis of multivariate analysis, such as factorial analysis, logistic regression and classification and regression trees (CART), are used to analyze the data. The results confirm (i) there is a positive relation between the entrepreneurial intention of the university students and the existence of their own businesses; (ii) there is a positive relationship between the country of origin of university students and their entrepreneurial intent; (iii) there is no positive relationship between the professional experience of university students and their entrepreneurial intention; (iv) there is a positive relationship between the sustainable behavior of university students and their entrepreneurial intent; (v) there is a positive relationship between the innovative behavior of university students and their entrepreneurial intent. In general, the results contribute to overcome the gap in the empirical literature that aligns phenomena such as entrepreneurship, innovation and sustainability, and this gives an innovative character to this study, which makes possible recommendations for future research.